(untitled) (European Journal of Economics, Finance and Business Development, 2023)
Enhancing the efficacy of small and private service-oriented businesses stands as a pivotal concern within the contemporary economic landscape, crucial for advancing the nation’s prosperity. A key focus lies in delineating pathways to elevate the operational efficiency of these entities, acknowledged as primary drivers of ownership and pivotal to augmenting organizational and economic frameworks. This necessitates the formulation of empirically grounded propositions and pragmatic recommendations. The evolution of market dynamics, coupled with ongoing economic liberalization, underscores the pivotal role played by small businesses and private entrepreneurship, integral to bolstering fiscal stability, amplifying Gross Domestic Product (GDP), and fostering employment opportunities. Facilitating an environment conducive to sectoral growth involves crafting favourable conditions, including tailored tax regimes, customs incentives, and adept utilization of financial instruments like bank loans. Consequently, this strategic alignment leads to a notable surge in the establishment and expansion of small businesses and private enterprises, bolstering their rapid proliferation.